Eight (8) rice varieties from CIAT/FLAR origin, available for farmers in Costa Rica, adapted to direct seeding planting system - CGIAR Research Program on Rice (2019)
These varieties are listed in the Commercial Varieties Registration Catalog of the National Seeds Office (From the Ministry of Agriculture). This catalog shows all varieties that are available for seeds production and commercialization in Costa Rica